2015
DOI: 10.1155/2015/470274
|View full text |Cite
|
Sign up to set email alerts
|

An Implicit Identity Authentication System Considering Changes of Gesture Based on Keystroke Behaviors

Abstract: Smartphones have become ubiquitous personal devices so that much of sensitive and private information will be saved in the phone, and users have their own unique behavioral characteristics when using smartphones, so, to prevent private information from falling into the hands of impostors, there is a kind of identity authentication system based on user's behavioral features while the user is unlocking. However, due to the impact of environmental factors, changes of gesture will introduce bias into the feature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
6

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
0
18
0
6
Order By: Relevance
“…to build the model, samples from both legitimate and illegitimate subjects are used. This is also the case for the work reported in papers (Buriro et al 2017;Ho 2013;Wu and Chen 2015). However, in real-life, as mobile devices are very much personal devices, illegitimate subject samples may not always be available.…”
Section: Related Workmentioning
confidence: 74%
See 1 more Smart Citation
“…to build the model, samples from both legitimate and illegitimate subjects are used. This is also the case for the work reported in papers (Buriro et al 2017;Ho 2013;Wu and Chen 2015). However, in real-life, as mobile devices are very much personal devices, illegitimate subject samples may not always be available.…”
Section: Related Workmentioning
confidence: 74%
“…By far, the best accuracy performance was reported by (Wu and Chen 2015). The authors achieved an EER value of 0.56%.…”
Section: Related Workmentioning
confidence: 98%
“…In addition, studies using both orientation and accelerometers have been researched. Xu et al [27] guessed the enter keys and showed 88.7% accuracy which is higher than the former study, and Wu and Chen [14] showed 0.556% EER using these two features and time, pressure, and size features. Table 1 shows the mobile keystroke dynamics studies.…”
Section: Related Workmentioning
confidence: 79%
“…Many researches make use of Android applications to collect activity data and use back‐end classifiers to identify activity classes. Activity recognition from sensors data is generally treated as a classification problem, with different authors proposing different machine learning approaches to its solution .…”
Section: Related Workmentioning
confidence: 99%